DEVELOPMENT OF A FUNDRAISING WEBSITE WITH PAYMENT GATEWAY TO SUPPORT DIGITAL ECONOMY AT LAZISMU - Pratama, Yudistira Bagus; Hevitria, Hevitria; Setiawan, Rifki Hanif (Jurnal Pilar Nusa Mandiri, 2025)
This study discusses digital-based fundraising and financial services in the management of zakat, infaq, and shadaqah (ZIS). In this process, strategies and data related to distribution, calculation, management, and disbursement of funds often pose challenges. This issue is particularly evident in LAZISMU Bangka Belitung, which has yet to establish a website for large-scale online fundraising and for providing information about its available programs.   Currently, the process of fundraising and ZIS management is still carried out conventionally. Therefore, this study proposes a digital system for LAZISMU that can provide information, manage ZIS, and facilitate digital payments through an integrated payment gateway. This innovation aims to make it easier for the public to fulfill their zakat obligations and access information about the fund distribution programs available at LAZISMU Bangka Belitung. The method used in developing this system is a prototype. The results of the study indicate that the developed system can simplify the process of fundraising and managing ZIS digitally. The implementation of this system is expected to enhance the efficiency of zakat management and have a broader positive impact in supporting communities in need.